Adobe Premiere Pro: Complete Course(photocopy) - L. Baker Donna (American : Wiley Publishing, 2004)
Text provides a complete course showing how to master the full range of Premiere Pro tools and techniques while working on a single project. Includes twelve sessions and more than eighty step-by-step tutorials. For beginning to intermediate users. Softcover.
Keywords: CD-ROM; Click the time indicator; Editing Video Clips; Spindown arrow